2020
DOI: 10.1101/2020.08.27.270504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic and transcriptomic profiling reveal different aspects of aging in the kidney

Abstract: The kidney is an excellent model for studying organ aging. Kidney function shows steady decline with age and is easy to assay using urine or blood samples. However, little is known about the molecular changes that take place in the kidney during the aging process. In order to better understand the molecular changes that occur with age, we measured mRNA and protein levels in 188 genetically diverse mice at ages 6, 12, and 18 months. We observed distinctive change in mRNA and protein levels as a function of age.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…Increase in immune cell composition across multiple tissues (Moro-García et al 2013;Müller-Werdan 2007) and up-regulation of immune response genes in the aging murine heart are well documented (Bartling et al 2019;Greenig et al 2020). We observe a marked increase in complement factor genes that is also seen in our previous study of aging kidney on the same mice (Takemon et al 2021) and in the proteome of human plasma (Johnson et al 2020). Complement factor 4B (C4b) is one of the transcripts with the highest change with age in our data.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Increase in immune cell composition across multiple tissues (Moro-García et al 2013;Müller-Werdan 2007) and up-regulation of immune response genes in the aging murine heart are well documented (Bartling et al 2019;Greenig et al 2020). We observe a marked increase in complement factor genes that is also seen in our previous study of aging kidney on the same mice (Takemon et al 2021) and in the proteome of human plasma (Johnson et al 2020). Complement factor 4B (C4b) is one of the transcripts with the highest change with age in our data.…”
Section: Discussionsupporting
confidence: 81%
“…To determine if the change in correlation of proteins with age is specific to the heart we repeated this analysis on data from kidney of the same DO mice (Takemon et al 2021). In kidney, there is a modest trend of increased correlation with age for proteins (Supplemental Figure S7A), suggesting that these age-related declines in protein complex correlations are tissue-specific.…”
Section: Loss Of Stoichiometry Occurs Across Multiple Protein Complex...mentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing both transcripts and proteins in the mouse heart we were able to detect distinct biological processes that are altered through the course of natural aging. We and others have found that age-related transcriptional changes are not necessarily followed by a change in their proteins and likewise, age-related changes in proteins are not preceded by transcriptional changes (12,13,62,80). We found that transcripts decreasing in expression with age are associated with cardiomyocyte contraction and survival, and fatty-acid metabolism.…”
Section: Discussionmentioning
confidence: 64%
“…Age-related dysregulation of transcripts is offset by selective translation, and post-transcriptional mechanisms become crucial for achieving cellular homeostasis (11). The investigation of molecular mechanisms involved in aging is further complicated by the uncoupling of age-related changes between transcripts and their corresponding proteins (12). Waldera-Lupa et al (2014) found that 77% of the proteins that change with age in human fibroblasts showed no corresponding change in their transcripts (13).…”
Section: Introductionmentioning
confidence: 99%